Mortality in psoriasis and psoriatic arthritis: systematic review and meta-analysis - Velásquez-Hernández, Karen Fabiola; Peralta-Pedrero, Maria Luisa; Velásquez-Hernández, Miriam de Jesús; Valderrama-Treviño, Alan Isaac; Morales-Sánchez, Martha Alejandra (International Journal of Research in Medical Sciences, 2021)
We had found contradictory results that have been reported in recent publications regarding the mortality risk of patients with psoriasis (Pso) and psoriatic arthritis (PsA). These patients have aggregated risk behaviors, which directly impacted their morbidity/mortality. We included 15 studies, with a total population of that reported mortality risk in Pso and PsA patients. We calculated crude mortality rate (CMR) of each one and pooled CMR by group and 95% confidence intervals (CI). The pooled CMR for Pso was 14/1000 (95% CI: 6-21%), 12/1000 (95% CI: 10-15%) in mild, 19/1000 (95% CI: 15-23%) in severe and 12/1000 was observed (95% CI: 10-14%) in PsA. Mortality was relatively higher in PsA patients when compared with Pso, with a RR of 1.03 (95% CI: 1.01-1.06, p<0.01). Pso was associated with increased mortality when compared to the general population. Mild Pso and PsA have the same increased mortality, then again as the severity of Pso increased, so does its mortality. The final comparative mortality between patients with PsA and those with Pso was around 3%.